Critical factors influencing the effectiveness of research teams among academicians - Wan Mohamed, M. F.; Omar, Zoharah; Ahmad, Aminah; Juned, Rusinah (Universiti Putra Malaysia Press, 2012)
Work team is one of the common methods of doing research nowadays. The concept of work teams is seen as a special application of groups in business, industry, government, as well as education and healthcare settings, which lies at the foundation of the modern organization. This method allows team members to save their energy, time and resources. There are a lot of models and theories discussed on the work team. However, little attention has been given to developing a model of research work team in academic setting. Looking into the academician career, there are some aspects which are different from those who work in industrial setting, particularly in terms of their needs, job load, resources and outcomes. This paper focuses on the factors needed for an effective research work team in the academic setting. Using semi-structured interviews, the author asked the following question, “Based on your experiences, what are the important factors needed for a research team to function effectively?” Three main themes emerged during the interviews, and these were leadership, team members and support. The discussion considers the experiences of the respondents when involving themselves in a research team. Further discussion shows how this issue can assist academicians to work better in a team and to get more satisfaction in the future.